Venous Thromboembolism in Patients Discharged after COVID-19 Hospitalization - Engelen, Matthias M.; Vandenbriele, Christophe; Balthazar, Tim; Claeys, Eveline; Gunst, Jan; Guler, Ipek; Jacquemin, Marc; Janssens, Stefan; Lorent, Natalie; Liesenborghs, Laurens; Peerlinck, Kathelijne; Pieters, Griet; Rex, Steffen; Sinonquel, Pieter; Van der Linden, Lorenz; Van Laer, Christine; Vos, Robin; Wauters, Joost; Wilmer, Alexander; Verhamme, Peter; Vanassche, Thomas (Seminars in Thrombosis and Hemostasis, 2021)
Background Venous thromboembolism (VTE) is a frequent complication of COVID-19, so that the importance of adequate in-hospital thromboprophylaxis in patients hospitalized with COVID-19 is well established. However, the incidence of VTE after discharge and whether postdischarge thromboprophylaxis is beneficial and safe are unclear. In this prospective observational single-center study, we report the incidence of VTE 6 weeks after hospitalization and the use of postdischarge thromboprophylaxis.Methods Patients hospitalized with confirmed COVID-19 were invited to a multidisciplinary follow-up clinic 6 weeks after discharge. D-dimer and C-reactive protein were measured, and all patients were screened for deep vein thrombosis with venous duplex-ultrasound. Additionally, selected high-risk patients received computed tomography pulmonary angiogram or ventilation–perfusion (V/Q) scan to screen for incidental pulmonary embolism.Results Of 485 consecutive patients hospitalized from March through June 2020, 146 patients were analyzed, of which 39% had been admitted to the intensive care unit (ICU). Postdischarge thromboprophylaxis was prescribed in 28% of patients, but was used more frequently after ICU stay (61%) and in patients with higher maximal D-dimer and C-reactive protein levels during hospitalization. Six weeks after discharge, elevated D-dimer values were present in 32% of ward and 42% of ICU patients. Only one asymptomatic deep vein thrombosis (0.7%) and one symptomatic pulmonary embolism (0.7%) were diagnosed with systematic screening. No bleedings were reported.Conclusion In patients who had been hospitalized with COVID-19, systematic screening for VTE 6 weeks after discharge revealed a low incidence of VTE. A strategy of selectively providing postdischarge thromboprophylaxis in high-risk patients seems safe and potentially effective.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; COVID-19; SARS-CoV-2; anticoagulation; thromboprophylaxis after discharge; postdischarge thromboprophylaxis